PENGARUH KETERAMPILAN KERJA, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN: Studi Pada Art Shop Akor Nature Bag Di Kerobokan Badung - Ni Kadek Ari Dipta Wardani; I Gede Aryana Mahayasa; I Komang Gede (Universitas Triatma Mulya, 2022)
This research was used to determine the influence of work skills, rewards and Punishments both partially and simultaneously on employee performance at the Art Shop Akor Nature Bag in Kerobokan Badung. This research was conducted at the Art Shop Akor Nature Bag in Kerobokan Badung with the number of population and the research sample was an employee at the Art Shop Akor Nature Bag in Kerobokan Badung, which was as many as 40 people using saturated sampling. The analysis techniques used are multiple linear regression analysis, determination coefficient test, T test and F test. The results of the study found that 1) Job skills had a positive and significant effect on employee performance with β1 = 0.246 and thitung values = 3,793 > ttabel = 2,028. 2) Rewards have a positive and significant effect on employee performance with β2 = 0.289 and thitung value = 2,214 > ttabel = 2,028. 3) Punishment has a positive and significant effect on employee performance with a value of β3 = 0.348 and a thitung value = 2.048 > ttabel = 2.028. 4) Job skills, rewards and Punishments have a positive and significant effect on employee performance with Ftabel = 2.84 < Fhicalc = 8,959. Advice given so that employees are able to better understand and master procedures that can be used to facilitate work, so as to improve employee performance.